Validity of Assessment Instruments for Students Creative Thinking Ability on Hydrocarbon Material - Elsa Magara; Jimmi Copriady; Roza Linda (STAI Hubbulwathan Duri, 2021)
This study aims to produce an assessment instrument to assess the ability to think creatively on hydrocarbon material and determine the validity of the assessment instrument. The research method used the research and development model of Borg and Gall. This research stage was carried out until the development stage. The assessment instrument developed in this study consisted of twenty-four items in the essay test, which referred to creative thinking indicators, which consisted of 4 indicators. Validation of the instrument for assessing the ability to think creatively was carried out by three validators with expert validity and validation of the measurement of creative thinking skills by experts measured using the Guttman scale. Based on the validity according to the expert, namely the material, construction and language aspects with the Aikens formula, it was obtained that the average expert validation ranged from 0.87 to 0.94 for the very good category, and 12 questions were declared valid. The validity of measuring the ability to think creatively using the Guttman scale obtained the results of 97.2% declared valid. 12 The developed test instrument is considered valid so that it can be used as a measuring tool to determine students' creative thinking abilities.